Implementation of Disciplinary Character Education: A Comparative Study of Indonesian and Japanese Primary School - Marcela, Intan Nur; Hidayat, Muhamad Taufik (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research aims to compare the implementation of disciplinary character education in elementary schools in Indonesia and Japan. Methodology: The method used in this research is descriptive qualitative with a literature study design and comparative literature review type. Data sources come from online journal articles, article websites, school websites, and YouTube videos. Results: The research results show that (1) Indonesian and Japanese elementary schools' school and class regulations exist. (2) There are regulations outside of learning in Indonesian and Japanese elementary schools. (3) Punishment in Indonesian elementary schools can use a points system, whereas Japanese elementary schools use a group peer pressure system. (4) Consistency in the form of habituation in Indonesian elementary schools is carried out through worship activities and daily notes. In contrast, in Japanese elementary schools, it is carried out through routine activities of cleaning the school (o- sōji), lunch (kyuushoku), and character education learning (doctors), and students are used to bying strict rules since childhood. (5) Student consistency in class in Indonesian and Japanese elementary schools is established through routine activities according to the learning sequence. Applications/Originality/Value: The novelty of this research is that this research compares the implementation of disciplined character education in Indonesian and Japanese elementary schools using the literature review method.